Seismic structure changes beneath Redoubt Volcano during the 2009 eruption inferred from local earthquake tomography. Issue 6 (12th June 2014) - Kasatkina, Ekaterina; Koulakov, Ivan; West, Michael; Izbekov, Pavel
Abstract We present seismic velocity models of the area beneath Redoubt Volcano (Alaska) corresponding to two time periods, before and after the strong eruption that occurred in March 2009. The calculations were based on tomographic inversion of P and S arrival time data recorded by 19 stations using the local earthquake tomography code LOTOS. We performed thorough analysis of the results based on synthetic tests in each of the time periods that allow real‐time variations in structure to be distinguished from artifacts caused by changes in the observation system configurations. In the resulting images corresponding to the period before the eruption, the summit area is characterized by higher values of both P and S velocities and moderate values of the Vp/Vs ratio. This may correspond to the rigid igneous rocks composing the body of the volcano that lack significant liquid content. In the second episode corresponding to the time of the eruption, the P velocity remained high, whereas the S velocity became very low. The anticorrelation of P and S anomalies in the summit area produced a Vp/Vs ratio as high as 2.2, which is seen down to 2–3 km depth. This indicates presence of mobile phase at shallow depth beneath the volcano, which can be either in the form of partial melt or fluid‐saturated rocks.